Evaluación y mejora de la adhesión terapéutica en los pacientes hipertensos - Saturno Hernández, P.J. (Aten Primaria, 2001)
OBJECTIVES: First, to assess whether it is useful for a patient to take part in the analysis of the causes of non-compliance with therapy for hypertension. Second, to design a questionnaire to evaluate the causes and the degree of adherence to therapy and to construct indicators on the basis of this. Lastly, to determine the effectiveness of the feedback of the evaluation of these indicators to health professionals, as a method of improving hypertense patients´ adherence to therapy. DESIGN: a) Qualitative study through the focus group technique; b) quasi-experimental design of independent samples between evaluation and re-evaluation with two study groups: experimental (3 PC health centres) and control (3 PC health centres). SETTING: PC health centres. PARTICIPANTS: Patients over 18 on medical hypertension treatment. MEASUREMENTS: First phase: analysis of the reasons for non-compliance with therapy through the group focus technique and design of the questionnaire to evaluate factors associated with non-compliance. Second phase: evaluation and pilot study of the questionnaire. For this, a questionnaire to assess therapy adherence and to determine the weight of related factors will be sent to a random sample of hypertense patients at each Health Centre. Third phase: intervention. A report with the results of the first assessment will be sent to the health professionals of the experimental group. Fourth phase: re-evaluation of the indicators of adherence, and analysis of the improvement achieved.